TWO-FACTOR AUTHENTICATION USING A EMV CHP CARD - Vakhrushev, P.A. (Perm Federal Research Centre Journal, 2015)
A computer program has been designed to implement two-factor user authentication when accessing sensitive information in the database. A bank card of EMV standard describing public keys infrastructure is used as the second authentication factor.